Effect of angled spray nozzle designs on spray distribution and droplet spectrum1 - Negrisoli, Matheus Mereb [UNESP]; De Souza, Diego Miranda; Rodrigues, Danilo Morilha [UNESP]; De Jesus, Patrick Julio [UNESP]; Raetano, Carlos Gilberto [UNESP] (GN1 Sistemas e Publicacoes, 2021)
New technologies have been developed to promote uniform, sustainable, safe and effective application of phytosanitary products. In this scenario, spray nozzles of different designs and jet angles can optimize application. Therefore, we aimed to analyze the effect of angled flat fan spray nozzles on spray pattern uniformity and droplet spectrum formation. The spray volumetric distribution of standard flat fan, double flat fan and the new angled flat fan spray nozzle, using two spray volumes were assessed. For that, the spray pattern distribution and the coefficient of variation (CV) were determined. The droplet spectrum characterization produced by the same treatments was performed in a real-time particle size analyzer. Also the effect of adding a fungicide mixture associated with an adjuvant on droplet formation was evaluated. All spray nozzles, regardless of design and spray volumes evaluated, produced CV values below 7%, considered acceptable by international uniformity standards. There was a difference in spray pattern according to the spray nozzle design and spray volume. It was evidenced that the main differences found in droplet spectrum occurred due to spray nozzle type, spray mixture and nominal flow rate, with little influence of spray jet angled or spray volumes.
Efeito de pontas de pulverização de jato angulado sobre a distribuição e espectro de gotas
Keywords: Angled flat fan. Uniformity of volumetric distribution. Droplet size. Volume median diameter; Jato plano angulado. Uniformidade de distribuição volumétrica. Tamanho de gotas. Diâmetro mediano volumétrico